AKTIVITAS HESPERIDIN SEBAGAI AGEN KOKEMOTERAPI BERTARGET P-GLIKOPROTEIN DAN IKK UNTUK MENGATASI RESISTENSI PADA SEL MCF-7 RESISTEN DOKSORUBISIN - , RIFKI FEBRIANSAH, Dr. Agung Endro Nugroho, M.Si., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Doxorubicin is a chemotherapeutic agent used to treat breast cancer, but it induces resistance in some cancers especially in breast cancer. One of the doxorubicin resistance mechanism was resulted from Pgp overexpression, which is an energy dependent pump effluxing xenobiotics out from cells. This study was aimed to overcome resistance of doxorubicin in MCF-7 resistant doxorubicin cells (MCF-7/Dox) with flavonoid active compound in citrus, hesperidin. The MCF-7 resistant doxorubicin (MCF-7/DOX) cells were maintained in 25 nM dox-contained medium for 5 weeks. The cytotoxic properties, 50% inhibition concentration (IC50) of hesperidin and its combination with doxo in MCF-7/DOX cells were determined using MTT assay. Apoptosis induction was examined by double staining assay using etidium bromide-acridine orange. Immunocytochemistry assay was performed to determine the level and localization of Pgp. For In silico study, docking PLANTS program was used to investigate the interaction of hesperidin on IKK and Pgp protein reseptor. Single treatment of hesperidin showed cytotoxic activity on MCF-7/DOX cells with IC50 value of 11 Î¼M. The combination treatment of hesperidin and doxorubicin showed additive and antagonist effect (CI>1,0). Hesperidin did not increase the apoptotic induction, but decreased the Pgp expressions level when combined with doxorubicin in low concentration. The result of in silico study showed that hesperidin has high affinity to interact with IKK and Pgp reseptor. This research indicated that hesperidin is potential to be applied as a chemopreventive agent in resistant breast cancer therapy.